2017
DOI: 10.1186/s13104-017-2644-3
|View full text |Cite|
|
Sign up to set email alerts
|

High rhesus (Rh(D)) negative frequency and ethnic-group based ABO blood group distribution in Ethiopia

Abstract: BackgroundKnowledge of the distribution of ABO-Rh(D) blood groups in a locality is vital for safe blood services. However, the distribution of these blood systems among Ethiopians in general is little explored. This study was, therefore, designed to determine the ABO-Rh(D) blood group distribution among patients attending Gambella hospital, southwestern Ethiopia.MethodsA cross-sectional study was conducted between November and December 2013 (N = 449). The patients were grouped into two broad categories. Those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 25 publications
9
53
5
Order By: Relevance
“…The predominance of the O phenotype observed in this study is common in other African populations, but there are some slight differences in the distribution of A and B phenotypes. The ABO distribution formula, O > A>B > AB, has also been reported from similar studies in other African countries (Apecu, Mulogo, Bagenda, & Byamungu, ; Golassa, Tsegaye, Erko, & Mamo, ; Hamed et al, ; Tagny, Fongué, & Mbanya, ; Tesfaye, Petros, & Andargie, ;). From studies reported so far from Africa, it is observed that the frequency of blood group A or B may be similar or show only marginal differences depending on the specific population in Africa.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The predominance of the O phenotype observed in this study is common in other African populations, but there are some slight differences in the distribution of A and B phenotypes. The ABO distribution formula, O > A>B > AB, has also been reported from similar studies in other African countries (Apecu, Mulogo, Bagenda, & Byamungu, ; Golassa, Tsegaye, Erko, & Mamo, ; Hamed et al, ; Tagny, Fongué, & Mbanya, ; Tesfaye, Petros, & Andargie, ;). From studies reported so far from Africa, it is observed that the frequency of blood group A or B may be similar or show only marginal differences depending on the specific population in Africa.…”
Section: Discussionsupporting
confidence: 71%
“…This study therefore supports the possibility of variations of blood groups amongst various ethnic groups in a population. Similarly, Golassa et al () reported that phenotypes “O” and “A” were dominant amongst the Nilotic natives and “highlanders,” respectively, within the population of Gambella Town in Ethiopia. Rhesus frequency distribution amongst the various ethnic groups was similar and had a comparable trend with the general population.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Beyond Nigeria, our findings agree with the findings of other investigators who reported similar patterns of gene frequencies for ABO blood groups in Uganda [14] , Ethiopia [26] , Tanzania [27] , Saudi Arabia [28] and Brazil [29] respectively. Our findings differ from one Pakistani study [30] and another India study [15] .…”
Section: Resultssupporting
confidence: 92%